Analisa Dan Pengembangan Aplikasi Buku Tamu Berbasis Web Pada Kelurahan Pondok Cabe Udik - Andini Selva Noviriliya; Meisya Andini; Selsa Bela Hutabarat; Wasis Haryono (CV. Multi Kreasi Media, 2022)
Along with the rapid advancement of information technology in various aspects of life in utilizing technological advances, especially at the Pondok Cabe Udik village office as in the reception of guests is still done manually and it takes a web-based application.The purpose of the website at Pondok Cabe Udik Village is to produce dynamic performance and be easy to update at any time, besides that this website can also be a means for Pondok Cabe Village. to provide alternative media that are easier to learn for the community. The conclusions in this study are: 1). By using this system user can save time inputting, editing and searching guest data. 2). The web system makes it easier to manage guest data. 3). Has several features in displaying reports as needed.